Impact of DRG Reform Policies on Hospitalization Costs of Stroke Patients in Western China: Wisdom from Traditional Chinese Medicine - Wang J; Chen M; Yang J (Risk Management and Healthcare Policy)
Jiayi Wang,1 Mengen Chen,2 Jingyu Yang1,3 1School of Health Management, Gansu University of Chinese Medicine, Lanzhou, People’s Republic of China; 2School of Traditional Chinese Medicine, Beijing University of Chinese Medicine, Beijing, People’s Republic of China; 3School of Public Health, Lanzhou University, Lanzhou, People’s Republic of ChinaCorrespondence: Jingyu Yang, School of Health Management, Gansu University of Chinese Medicine, 35 Dingxi East Road, Chengguan District, Lanzhou, Gansu, 730000, Email yjy19680326@163.comBackground: Stroke presents a significant economic burden worldwide, with the impact being especially pronounced in developing countries. China is currently implementing Diagnosis-Related Group (DRG) reforms, attempting to use more traditional Chinese medicine (TCM) modalities to alleviate the economic burden on stroke patients.Methods: This retrospective study extracted the medical records of stroke inpatients at Qingyang City Hospital of TCM from 2017 to 2022 from China’s Gansu National Health Big Data Platform. A single-group interrupted time series (ITS) design was employed to assess the impact of DRG reform on patients’ hospitalization costs and length of stay (LOS). Additionally, a two-group ITS was utilized to evaluate treatment costs and medicine costs.Results: The single-group ITS analysis indicated that the average LOS decreased by 0.06 days per month following the reform (P < 0.05), while the average hospitalization cost declined by 48.92 yuan per month (P < 0.05). The two-group ITS results revealed a significant reduction in the average monthly cost of Western medicine by 22.67 yuan post-reform (P < 0.05), whereas the average monthly cost of Chinese medicine increased by 2.93 yuan, though this change was not statistically significant (P > 0.05). Additionally, the average monthly cost of Western medical treatment decreased by 11.24 yuan (P < 0.05). Acupuncture and massage treatment costs exhibited an initial sharp increase followed by a downward trend, with an average monthly decrease of 9.53 yuan (P < 0.05).Conclusion: DRG reduced hospitalization costs and shortened the LOS of stroke patients, which may be related to the increased use of TCM in stroke treatment.Keywords: DRG, stroke, Chinese medicine cost, acupuncture and massage treatment cost, ITS